Search for single production of vector-like quarks decaying to a top quark and a W boson in proton-proton collisions at TeV - Sirunyan, A. M. (2019)
A search is presented for the single production of vector-like quarks in proton-proton collisions at TeV. The data, corresponding to an integrated luminosity of 35.9fb-1, were recorded with the CMS experiment at the LHC. The analysis focuses on the vector-like quark decay into a top quark and a W boson, with one muon or electron in the final state. The mass of the vector-like quark candidate is reconstructed from hadronic jets, the lepton, and the missing transverse momentum. Methods for the identification of b quarks and of highly Lorentz boosted hadronically decaying top quarks and W bosons are exploited in this search. No significant deviation from the standard model background expectation is observed. Exclusion limits at 95% confidence level are set on the product of the production cross section and branching fraction as a function of the vector-like quark mass, which range from 0.3 to 0.03pb for vector-like quark masses of 700 to 2000GeV. Mass exclusion limits up to 1660GeV are obtained, depending on the vector-like quark type, coupling, and decay width. These represent the most stringent exclusion limits for the single production of vector-like quarks in this channel.